Sexual Violence and Gender Equality in Grassroots Music Venues: How to Facilitate Change - Hill, Rosemary Lucy; Megson, Molly (IASPM Journal, 2020)
Sexual violence in the music industry is known to impact negatively on women’s participation. We examine how grassroots venues and promoters can implement changes to tackle sexual violence and work towards gender equality. We draw on UK-based, impact-focused research which sought to raise awareness of sexual violence, and to facilitate anti-violence changes within organisations. We find that working across a city’s music scene and engaging with oversight organisations such as local authorities can aid in persuading venues and promoters to seek training. However, for individuals leading on changes, personal experiences of sexual violence as a victim/survivor or bystander are important factors in their decision. We conclude that men in the music industry need to become more aware of the need for change, and willing to act on that awareness; and that more women need to own, manage, and run venues and events.
Keywords: Bibliographie; Gender; Nettoyer; live music; music industry; music venues; prevention; sexual violence

Sexual violence at live music events: Experiences, responses and prevention - Hill, Rosemary Lucy; Hesmondhalgh, David; Megson, Molly (International Journal of Cultural Studies, 2020)
Recent media reporting has highlighted that incidents of sexual violence frequently occur at live music events. Sexual violence has significant impacts on the health of those who experience it, yet little is known of how it impacts on everyday engagements with music, nor what measures venues and promoters might take to prevent and respond to incidents. Through interviews with concert goers, venue managers, promoters and campaigning groups, we investigated experiences of sexual violence at indie, rock, punk and funk gigs in small venues in one English city. We show that sexual violence at live music events significantly impacts on (predominantly) women’s musical participation. We argue that venues and promoters must work proactively to create musical communities that act as a defence against the normalisation of sexual violence, taking inspiration from safer space policies.
Keywords: Camille; gender; live music; prevention; safe spaces; sexual violence; unwanted sexual attention

Cultural value and cultural policy: some evidence from the world of live music - Behr, Adam; Brennan, Matt; Cloonan, Martin (International Journal of Cultural Policy, 2016)
This article considers live music policy in relation to wider debates on the cultural (as opposed to instrumental) value of the arts. The findings are based on research into amateur/enthusiast, state-funded and commercial concerts across a range of genres – classical, traditional folk, jazz, singer–songwriter and indie – using the Edinburgh Queen’s Hall venue as a case study. We argue that (1) articulations of the cultural or intrinsic value of live music across genres tend to lapse back into descriptions of instrumental value; (2) although explanations vary from audiences, artists and promoters as to why they participate in live music, they also share certain characteristics across genres and sometimes challenge stereotypes about genre-specific behaviours; and (3) there are lessons to be learned for live music policy from examining a venue that plays host to a range of genres and promotional practices.
Keywords: audience research; cultural value; live music; music policy; regulation